Rosai-Dorfman Disease Originating from Nasal Septal Mucosa - Akyigit, Abdulvahap; Akyol, Hadice; Sakallioglu, Oner; Polat, Cahit; Keles, Erol; Alatas, Ozkan (Hindawi Ltd, 2015)
Rosai-Dorfman disease is a rarely seen disease with unknown etiology. Extranodal involvement is most commonly seen in the head and neck region. Histopathologically, it is characterized by histiocytic cell proliferation. This paper presents a case of a 15-year-old male patient who presented with nasal obstruction and was surgically treated for a mass filling in the left nasal meatus that was diagnosed to be Rosai-Dorfman disease by histopathological examination.
Keywords: Sinus Histiocytosis; Massive Lymphadenopathy